2014
DOI: 10.1111/obr.12170
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non‐surgical weight loss interventions on urinary incontinence in overweight women: a systematic review and meta‐analysis

Abstract: Although the aetiology of urinary incontinence can be multifactorial, in some cases weight loss could be considered as a part of the therapeutic approach for urinary incontinence in people who are overweight. The objective of this study was to review and meta-analyse the effect of non-surgical weight loss interventions on urinary incontinence in overweight women. Web of Science, PubMed, Pedro, SPORTDiscus and Cochrane were systematically searched for clinical trials that met the a priori set criteria. Data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…29 A recent systematic review showed that a non-surgical weight loss intervention improves urinary incontinence and should be standard practice in the management of urinary incontinence in overweight women. 30 An association between UI and multimorbidity was also present in a North American study investigating 6,000 women. In that study, an OR ¼ 1.39 was found in women with comorbidities, confirming the increased risk of UI among women with other chronic diseases.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…29 A recent systematic review showed that a non-surgical weight loss intervention improves urinary incontinence and should be standard practice in the management of urinary incontinence in overweight women. 30 An association between UI and multimorbidity was also present in a North American study investigating 6,000 women. In that study, an OR ¼ 1.39 was found in women with comorbidities, confirming the increased risk of UI among women with other chronic diseases.…”
Section: Discussionmentioning
confidence: 81%
“…These are important data, since obesity is a risk factor liable to modification, either in the appearance of the disorder or in the successful treatment of obesity, which can be both clinical and surgical . A recent systematic review showed that a non‐surgical weight loss intervention improves urinary incontinence and should be standard practice in the management of urinary incontinence in overweight women …”
Section: Discussionmentioning
confidence: 99%
“…In addition, female UI is also related with other factors such as parity, type of delivery, previous hormone therapy and urogenital surgery, constipation, existence of pelvic floor disorders or other chronic diseases [29,31,[38][39][40]. Non-surgical weight loss interventions (diet, exercise or a combination of both) may improve female UI [41] and recently it has been shown that under extreme obese conditions, bariatric surgery has been proposed to improve urinary continence [42].…”
Section: Discussionmentioning
confidence: 98%
“…Obesity is also associated with UI, including stress and urgency UI subtypes, in epidemiological studies and clinical trials . There is evidence from several clinical trials that weight loss in persons with diabetes mellitus and obese women decreases the severity of UI symptoms …”
Section: Ui and Common Pathwaysmentioning
confidence: 99%